Description of the proton and neutron radiative capture reactions in the Gamow shell model - Fossez, K. (2015)
We formulate the Gamow shell model (GSM) in coupled-channel (CC) representation for the description of proton/neutron radiative capture reactions and present the first application of this new formalism for the calculation of cross sections in mirror reactions Be7(p,γ)B8 and Li7(n,γ)8Li. The GSM-CC formalism is applied to a translationally invariant Hamiltonian with an effective finite-range two-body interaction. Reactions channels are built by GSM wave functions for the ground state 3/2− and the first excited state 1/2− of Be7/Li7 and the proton/neutron wave function expanded in different partial waves.